Analysis of the Impact of KAP Reputation, Profitability, Institutional Ownership, and Audit Committee on Audit Report LAG - Heru (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to investigate the impact of public accounting firm (KAP) reputation, profitability, institutional ownership, and the existence of audit committees on audit report lag in publicly listed businesses within the primary consumer goods sector on the Indonesia Stock Exchange. This study adopts a quantitative research methodology, utilizing multiple linear regression analysis and gathering data through documentary research. The study population comprises 131 enterprises, from which a purposive sampling technique was employed to choose 87 sample entities. The data processing and analysis included descriptive statistics, diagnostic evaluation of classical assumptions, multiple linear regression modeling, determination of the coefficient of determination, and hypothesis testing. The empirical findings indicate that the reputation of the KAP, profitability, institutional ownership, and the audit committee have a statistically significant negative impact on audit report latency. The modified R-squared value of 0.252 signifies that around 25.2% of the variance in audit report latency is explained by the independent variables, while the remaining 74.8% is due to external factors not considered in this study. The author recommends that future research consider the addition of moderating or intervening variables, such as audit quality, company size, or operational complexity, to obtain more comprehensive results.